Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jcot.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Results of ring (Ilizarov) fixator in high energy Schatzker type VI fractures of proximal tibia

Abstract: The technique is well suited for the management of complex fractures of the proximal tibia (Schatzker VI) when extensive comminution at the fracture site and compromise of the soft tissue is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 32 publications
0
20
1
7
Order By: Relevance
“…A recent study also allowed immediate weight bearing as tolerated specifically in Schatzker type 6 fractures. 40 In Keightley et al 19 the mean ROM achieved was 110 degrees with one patient having a fixed flexion deformity of >10 degrees.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study also allowed immediate weight bearing as tolerated specifically in Schatzker type 6 fractures. 40 In Keightley et al 19 the mean ROM achieved was 110 degrees with one patient having a fixed flexion deformity of >10 degrees.…”
Section: Discussionmentioning
confidence: 95%
“…Keightley et al reported good long-term healing and functional outcomes in Schatzker type IV-VI tibial plateau fractures treated with an Ilizarov technique [ 16 , 17 ]. Debnath et al recommended the Ilizarov technique for Schatkzer type VI tibial plateau fractures with comminution [ 18 ]. Reddy et al reported good healing rates and low incidence of infection in Schatzker type II and above tibial plateau fractures [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Debnath et al [ 21 ], Gill and Raza [ 22 ], Zhao et al [ 23 ], and Nesari et al [ 24 ] believe that the Ilizarov technique is better for the management of complex tibial plateau fractures, which have extensive comminution with compromise of soft tissue and should be preferred over other methods. Whereas Tahir et al [ 25 ], Pineda et al [ 26 ], Metcalfe et al [ 27 ], and Boutefnouchet et al [ 28 ] believe that mode of fixation (ORIF or Ilizarov ring fixator) do not make any difference in the outcome.…”
Section: Discussionmentioning
confidence: 99%